Glycyrrhiza plastid paternal inheritance and a new DNA barcode provide new strategies for molecular identification of three medicinal licorice hybrid complexes - Jiafen Luo; Xuerong Zheng; Qian Xin; Mengnan Liu; Jie Zhang; Wenqing Chen; Chaonan Chen; Chaoyue Zhang; Guigui Wan; Caixia Xia; Jiahui Lu (BMC Plant Biology)
Abstract Background The widespread hybridization and introgression of Glycyrrhiza L. medicinal plants (Glycyrrhiza uralensis Fisch., Glycyrrhiza inflata Bat., and Glycyrrhiza glabra L.) complicate their classification and identification, thereby hindering the effective utilization of medicinal resources. Therefore, this study aimed to develop an efficient identification system to distinguish the three medicinal Glycyrrhiza species and their hybrid complexes. Results Through morphological analysis of 345 samples from natural hybrid zones of three medicinal Glycyrrhiza species, this study identified five representative hybrid morphological phenotypes from hybrid complexes with interspecific mosaic characteristics, providing a morphological foundation for identifying hybrid complexes. However, it still has significant limitations to rely solely on morphological traits to determine the parental origins of hybrid complexes. To address this, high-throughput sequencing of parents and progeny from artificial reciprocal cross-experiments was performed, generating eight chloroplast genomes and identifying a plastid paternal inheritance mode, Glycyrrhiza, through comparative analysis of variation sites. Additionally, the DNA barcode ndhA was screened from hypervariable regions within 12 chloroplast genomes to distinguish between the three medicinal Glycyrrhiza species. Using these findings, a new identification system incorporating ndhA, ITS, and trnH-psbA was developed to identify parents and introgression types in 52 samples. It efficiently and accurately identified the three medicinal Glycyrrhiza species and their interspecific hybridization introgression types, achieving a species resolution of 98.08%, which surpassed the two older systems (ITS + trnH-psbA + rbcL + matK and ITS + trnH-psbA + rbcL + matK + trnV-ndhC) and represents the best currently available identification method. Furthermore, phylogenetic trees were constructed using chloroplast genomes, and the new system revealed that their paternal lineage influenced the position of the hybrid complexes in the phylogenetic tree. Conclusions In summary, this study resolved the parent origin, species identification, and phylogenetic relationships of Glycyrrhiza hybrid complexes through morphological observations, plastid inheritance mode, high-resolution chloroplast barcode ndhA, and a novel molecular identification system. These findings enhance our understanding of hybrid complexes, facilitating the optimized utilization of resources while ensuring the medicinal material’s origin.